HERITABILITAS, NISBAH POTENSI, DAN HETEROSIS KETAHANAN KEDELAI (Glycine max [L.] Merrill) TERHADAP SOYBEAN MOSAIC VIRUS - Nyimas Sa’diyah; Hasriadi Mat Akin; Ria Putri; Risa Jamil; Maimun Barmawi (Universitas Lampung, 2016)
Heritability, potential ratio, and heterosis of soybean (Glycine max [L.] Merrill) resistance to soybean mosaic virus. The use of soybean cultivars with resistance to SMV is a way for controlling soybean mosaic disease. The objective of this research was to estimate the disease severity, the narrow sense heritability, potential ratio and heterosis of resistance character and number of pithy pods, number of healthy seeds, and healthy seeds weight per plant of ten F1 populations of soybean crossing result to SMV infection. The experiment was arranged in a randomized complete block design in two replications. Observed characters were disease severity, number of pithy pods, number of healthy seeds, and healthy seeds weight per plant. The result of this research showed that 1) the crossing combinations those which were resistant to SMV (lower disease severity) were Yellow Bean x Tanggamus, Tanggamus x Orba, and Tanggamus x Taichung, 2) the narrow sense heritability of disease severity was included in medium criteria, 3) number of pithy pods belonged to high criteria, and 4) number of healthy seeds and healthy seeds weight per plant were included in low criteria. The crossing combinations that had low estimationÂ value of heterosis and heterobeltiosis of resistance to SMV infection were Yellow Bean x Taichung, Bean x Tanggamus and Tanggamus x B3570. Disease severity or resistance to SMV is influenced by genetic and environmental factors.